2003
DOI: 10.1029/2003gl017024
|View full text |Cite
|
Sign up to set email alerts
|

Increasing background ozone during spring on the west coast of North America

Abstract: Using a 15‐year record of O3 from Lassen Volcanic National Park, a rural elevated site in northern California, data from two aircraft campaigns conducted in 1984 and 2002 over the eastern North Pacific, and observations spanning 18 years from five U.S. west coast, marine boundary layer sites, we show that O3 in air arriving from the Eastern Pacific in spring has increased by approximately 10 ppbv, i.e. 30% from the mid 1980s to the present. This positive trend in O3 correlates with the increasing trend in glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 14 publications
16
153
0
Order By: Relevance
“…The 'background' seasonal cycle at Arosa was very similar to that at Mace Head, suggesting a regional scale pattern of concentration in unpolluted air. Similar trends to those reported for western Europe are seen at the west coast of North America, where 7 out of 9 sites showed an average O 3 increase between 1987 and 2004 of 0.26 ppb y -1 (Jaffe et al, 2003;Jaffe and Ray, 2007). No trends could be seen in vertical profiles from ozonesonde measurements, but this was attributed to the variability in the data set caused by irregular sampling intervals.…”
Section: Evidence For Recent Trends In Ground-level Ozone Concentrationssupporting
confidence: 67%
“…The 'background' seasonal cycle at Arosa was very similar to that at Mace Head, suggesting a regional scale pattern of concentration in unpolluted air. Similar trends to those reported for western Europe are seen at the west coast of North America, where 7 out of 9 sites showed an average O 3 increase between 1987 and 2004 of 0.26 ppb y -1 (Jaffe et al, 2003;Jaffe and Ray, 2007). No trends could be seen in vertical profiles from ozonesonde measurements, but this was attributed to the variability in the data set caused by irregular sampling intervals.…”
Section: Evidence For Recent Trends In Ground-level Ozone Concentrationssupporting
confidence: 67%
“…The earliest O 3 data from 1985 were collected by one of the groups involved in the 2002 study. We are confident that systematic errors in the O 3 measurements make negligible contributions to the temporal trend reported by Jaffe et al [2003]. The precision of the data points used here is within ±2% or 1 ppbv, whichever is greater.…”
Section: Data Sets and Methods Utilizedmentioning
confidence: 55%
“…Consequently, we will investigate the relationships between measured concentrations of different species through logarithmic plots and perform linear, least squares fits to log transformed concentrations. [15] Figure 3 shows the coastal marine O 3 measurements discussed by Jaffe et al [2003], who concluded that the O 3 levels in air arriving at the U.S. West Coast have increased by about 30% over the past two decades. This increase is evident in the slopes of the temporal trend lines in Figure 3, which are summarized in Table 2.…”
Section: Data Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…'Acid rain' and ozone are the most studied secondary pollutants, as far as forest effects are concerned, and while amounts of wet-deposited acidity (and sulphate and nitrate) have decreased, there are still large areas of Europe and North America that exceed the Critical Loads for forests (Hettelingh et al, 1995). Moreover, the increasing industrialisation of India, China and south-east Asia is leading to a gradual increase in the 'background' concentrations of ozone across the northern hemisphere, with several studies demonstrating that long-range (intercontinental) transport of ozone and/or its precursors is affecting annual average ozone concentrations across the whole hemisphere (Auvray and Bey, 2005, Derwent et al, 2006, Jaffe et al, 2003, Jonson et al, 2006, Oltmans et al, 2006, Vingarzan, 2004. This gradual increase in 'background' ozone is set against a pattern of decreasing severity of peak ozone concentrations during episodes, which can be attributed to the effects of emission controls, particularly on VOCs (Derwent et al, 2003).…”
Section: Introductionmentioning
confidence: 99%